Granulocyte-colony stimulating factor (G-CSF) to treat acute-on-chronic liver failure: A multicenter randomized trial (GRAFT study) - Engelmann, Cornelius; Herber, Adam; Franke, Annegret; Bruns, Tony; Reuken, Philipp Alexander; Schiefke, Ingolf; Zipprich, Alexander; Zeuzem, Stefan; Goeser, Tobias; Canbay, Ali E.; Berg, Christoph; Trebicka, Jonel; et al. (Hepatology, 2021)
Background & Aims - Based on positive results from small single center studies, granulocyte-colony stimulating factor (G-CSF) is being widely used for the treatment of patients with acute-on-chronic liver failure (ACLF). Herein, we aimed to evaluate the safety and efficacy of G-CSF in patients with ACLF. - Methods - In this multicenter, prospective, controlled, open-label phase II study, 176 patients with ACLF (EASL-CLIF criteria) were randomized to receive G-CSF (5 μg/kg daily for the first 5 days and every third day thereafter until day 26) plus standard medical therapy (SMT) (n = 88) or SMT alone. The primary efficacy endpoint was 90-day transplant-free survival analyzed by Cox regression modeling. The key secondary endpoints were overall and transplant-free survival after 360 days, the development of ACLF-related complications, and the course of liver function scores during the entire observation period. - Results - Patients treated with G-CSF had a 90-day transplant-free survival rate of 34.1% compared to 37.5% in the SMT group (hazard ratio [HR] 1.05; 95% CI 0.711-1.551; p = 0.805). Transplant-free and overall survival at 360 days did not differ between the 2 arms (HR 0.998; 95% CI 0.697-1.430; p = 0.992 and HR 1.058; 95% CI 0.727-1.548; p = 0.768, respectively). G-CSF did not improve liver function scores, the occurrence of infections, or survival in subgroups of patients without infections, with alcohol-related ACLF, or with ACLF defined by the APASL criteria. Sixty-one serious adverse events were reported in the G-CSF+SMT group and 57 were reported in the SMT group. In total, 7 drug-related serious adverse reactions occurred in the G-CSF group. The study was prematurely terminated due to futility after conditional power calculation. - Conclusions - In contrast to previous findings, G-CSF had no significant beneficial effect on patients with ACLF in this multicenter controlled trial, which suggests that it should not be used as a standard treatment for ACLF. - ClinicalTrials.gov number - NCT02669680 - Lay summary - Granulocyte-colony stimulating factor was considered as a novel treatment for acute-on-chronic liver failure (ACLF). We performed the first randomized, multicenter, controlled phase II trial, which showed that G-CSF did not improve survival or other clinical endpoints in patients with ACLF. Therefore, G-CSF should not be used to treat liver disease outside clinical studies.
Gesehen am 21.01.2022